Buddhas & ancestors : religion and wealth in fourteenth-century Korea - Ahn, Juhn Young; ProQuest (Firm) (Seattle : University of Washington Press, 2018)
Two issues central to the transition from the Kory to the Chos n dynasty in fourteenth-century Korea were social differences in ruling elites and the decline of Buddhism, which had been the state religion. In this revisionist history, Juhn Ahn challenges the long-accepted Confucian critique that Buddhism had become so powerful and corrupt that the state had to suppress it. When newly rising elites (many with strong ties to the Mongols) used lavish donations to Buddhist institutions to enhance their status, older elites defended their own adherence to this time-honored system by arguing that their donations were linked to virtue. This emphasis on virtue and the consequent separation of religion from wealth facilitated the Confucianization of Korea and the relegation of Buddhism to the margins of public authority during the Chos n dynasty.
Introduction -- Sowing the seeds of salvation with wealth -- Dark and mysterious ways -- This way of ours -- All the king's men -- Buddhas and ancestors -- Conclusion -- Notes -- Glossary of Chinese characters -- Bibliography -- Index.
Includes bibliographical references and index.
Description based on online resource; title from digital title page (viewed on July 02, 2018).
eBooks on EBSCOhost
Keywords: Korea -- Religious life and customs; Wealth -- Religious aspects -- Buddhism; Wealth -- Religious aspects -- Confucianism; Buddhism -- Korea -- Customs and practices; Buddhist funeral rites and ceremonies -- Korea; Confucianism -- Korea -- Customs and practices; Funeral rites and ceremonies, Confucian -- Korea; Korea -- Civilization -- 935-1392.; Corée -- Vie religieuse; Richesse -- Aspect religieux -- Bouddhisme; Richesse -- Aspect religieux -- Confucianisme; Bouddhisme -- Corée -- Coutumes et pratiques; Funérailles -- Rites et cérémonies bouddhiques -- Corée.; Confucianisme -- Corée -- Coutumes et pratiques; Funérailles -- Rites et cérémonies confucéens -- Corée.; Corée -- Civilisation -- 935-1392.; RELIGION / Comparative Religion; HISTORY / Asia / Korea; Wealth -- Religious aspects -- Confucianism; Wealth -- Religious aspects -- Buddhism; Funeral rites and ceremonies, Confucian; Confucianism -- Customs and practices; Civilization; Buddhist funeral rites and ceremonies; Buddhism -- Customs and practices; Korea; Richesse -- Aspect religieux -- Confucianisme; Richesse -- Aspect religieux -- Bouddhisme; Rites et ceremonies funeraires -- Coree -- 14e siecle; Coree -- Civilisation -- 935-1392.; 935-1392